Full Potential Linearized Augmented Plane Wave Calculations of Electron and Positron Energy Levels in TlBr and TlCl - Bousahla Mohammed Alaa; Bousahla Mohammed Nadir; Bousahla Zouaoui; Khachai Houari; Bendjilali Hadjer; Benkatlane Aissa (Annals of West University of Timisoara: Physics, 2023)
Theoretical research was conducted on the energy levels of electrons and positrons in zinc-blend TlBr and TlCl using the first-principle full potential linearized augmented plane wave method based on the gradient generalized approximation GGA. The study involved the calculation of electron and positron band structures which provided predictive data on several properties such as positron mobility, positron affinity, diffusion constants, effective masses, and positronium work function.